The Effects Of Work Discipline On High Employee Performance - et. al., Anton Budi Santoso, (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2021)
This research aims to determine to what extent the work discipline factor can affect the increase in employee performance at BPJS Ketenagakerjaan at the Bandung Soekarno Hatta Branch Office. As for the population in this study are all employees who work in this company with the number of samples taken as much as the population. which amounts to 35 employees. Therefore, the sampling technique used in this study is saturated sampling (census). For the research method used, namely in the form of descriptive statistical analysis methods and verification. Meanwhile, simple linear regression analysis is a data processing and analysis technique which is calculated using the help of statistical tools in the form of the SPSS 20 for Windows software program. Based on the research results obtained, it is concluded that work discipline has a significant effect on employee performance. Thus, it is stated that the higher the level of discipline of employees at work which is shown through work behavior that is always obedient to all kinds of norms and regulations that apply in the company, the employees can show better work results.